Mary Joe Petree, Louise Brock, Janie Hanes, and Martha Morefield are caught in the rain on Country Club Road, 1964. - (:unkn) unknown (Forsyth County Public Library)
WSJ 8-13-64 p.1.
Mary Joe Petree, Louise Brock, Janie Hanes, and Martha Morefield are caught in the rain on Country Club Road, 1964.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth